Control of ZCZVT Commutation Cell Inverter - Thejel, Rabee' Hashim (Iraqi Journal for Electrical and Electronic Engineering, 2006)
This paper proposes a new control circuit to control the switching of the main switches of the used Zero Current Zero Voltage Transition (ZCZVT) inverter to ensure Zero Current and Zero Voltage Switching (ZCZVS). The reverse recovery losses of the main diodes are minimized and the auxiliary switches of the commutation cell are turned on at Zero Current Switching (ZCS) and off at ZCZVS. The commutation losses are practically reduced to zero due to ZCS. Sinusoidal Pulse Width Modulation (SPWM) is used to perform the switching of the power semiconductor devices and to control the output voltage value. MATLAB software is used to simulate the inverter circuit. Simulation results are presented to demonstrate the feasibility of the proposed control circuit.